2019
DOI: 10.1111/hepr.13337
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tolvaptan on the prognosis of patients with hepatic ascites

Abstract: Aim Despite accumulating evidence concerning the efficacy of tolvaptan in the treatment of body fluid retention or hyponatremia, the effect of tolvaptan on the prognosis of patients with hepatic ascites has not been fully investigated. Methods A total of 628 patients with hepatic ascites who were treated with diuretics (furosemide, spironolactone, or tolvaptan) between 2007 and 2017 were enrolled and divided into two groups: those who received tolvaptan (original tolvaptan group, n = 278) and those who did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 43 publications
(96 reference statements)
2
16
1
Order By: Relevance
“…Tolvaptan also reduced the clinical symptoms that otherwise impact a patient's survival, functional capacity, and QOL [22]. The findings of the current study are further supported by the results from recent studies, where treatment with tolvaptan improved Table 3 Incidence rate of adverse drug reactions by the timing of occurrence reported by physicians (C 0.5%) Spironolactone: androgen deprivation therapy equivalent J Gastroenterol the prognosis in liver cirrhosis patients with ascites [23][24][25].…”
Section: Discussionsupporting
confidence: 83%
“…Tolvaptan also reduced the clinical symptoms that otherwise impact a patient's survival, functional capacity, and QOL [22]. The findings of the current study are further supported by the results from recent studies, where treatment with tolvaptan improved Table 3 Incidence rate of adverse drug reactions by the timing of occurrence reported by physicians (C 0.5%) Spironolactone: androgen deprivation therapy equivalent J Gastroenterol the prognosis in liver cirrhosis patients with ascites [23][24][25].…”
Section: Discussionsupporting
confidence: 83%
“…11 On the other hand, treatment with tolvaptan has been associated with increased liver toxicity, 12 which may be caused by direct DNA damage and by delayed progression of the cell cycle and induction of apoptosis in hepatocytes. 14 However, up to 30% of patients fail to achieve satisfactory response to tolvaptan administration in terms of increased urination or bodyweight reduction. 14 However, up to 30% of patients fail to achieve satisfactory response to tolvaptan administration in terms of increased urination or bodyweight reduction.…”
Section: Introductionmentioning
confidence: 99%
“…13 It has been recently proposed that tolvaptan represents a promising add-on treatment in patients with refractory ascites due to liver cirrhosis, as it has been shown not only to correct hyponatremia but also to improve long-term prognosis. 14 However, up to 30% of patients fail to achieve satisfactory response to tolvaptan administration in terms of increased urination or bodyweight reduction. 15 Several observational studies have evaluated potential prognostic factors of tolvaptan response, although no consensus exists regarding the most efficient predictive model.…”
Section: Introductionmentioning
confidence: 99%
“…Vaptans are selective antagonists of the vasopressin 2 (V2) receptors in the principal cells of the collecting ducts that enhance solute‐free water excretion and thus raise serum sodium levels . For example, tolvaptan has been shown to have a survival‐benefit compared to control . Additionally, a phase 2 trial has shown that tolvaptan significantly reduced the body weight and abdominal circumference compared to placebo in patients with liver cirrhosis‐associated ascites .…”
Section: Management Of Portal Hypertension In Pldmentioning
confidence: 99%
“…53 For example, tolvaptan has been shown to have a survival-benefit compared to control. 57 Additionally, a phase 2 trial has shown that tolvaptan significantly reduced the body weight and abdominal circumference compared to placebo in patients with liver cirrhosis-associated ascites. 58 Another randomized trial showed that a combination of conventional natriuretic drugs and tolvaptan was superior to conventional therapy alone in cirrhosis-associated ascites.…”
Section: Management Of Ascitesmentioning
confidence: 99%